1999
DOI: 10.1002/(sici)1521-4044(19990401)50:4<156::aid-apol156>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Grafted carbon fibers and their physico-chemical properties. Part IV: Grafting of cyano-biphenyl containing liquid-crystalline monomers onto modified carbon fibers

Abstract: A simple, reproducible, already introduced grafting method of methacrylic monomers onto carbon fibers is applied to cyano‐biphenyl containing liquid crystalline (lc) monomers. The development of lc phases is faster and more uniform in the presence of carbon fibers. Applying a voltage to the grafted carbon fibers, causes phase transitions of the liquid crystals. By varying spacer length of the grafted lc polymers the physico‐chemical properties, e. g. wetting and electrokinetic behavior (zeta‐potential) are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…However, if one is aiming to covalently attach polymeric coatings or interlayers to carbon fiber surfaces, there are only three methods available: plasma polymer deposition [12][13][14][15][16][17], electropolymerization or -deposition [8][9][10][11]18], and in situ chemical grafting reactions [19][20][21][22][23][24]. In earlier studies, we showed that it is possible to tune the carbon fiber chemistry and functionality and thereby their surface properties, i.e., hydrophilic/ hydrophobic character, by grafting suited monomers such as methacrylic acid (MAA) [25], 2-(N,N-dimethylamino) ethyl methacrylate (DMAEMA) [26] and various liquid crystalline monomers [27,28] onto carbon fibers via simple free radical bulk polymerization in the presence of the carbon fibers. The degree of grafting onto the surfaces can be adjusted by the amount of initiator used [29].…”
Section: Introductionmentioning
confidence: 99%
“…However, if one is aiming to covalently attach polymeric coatings or interlayers to carbon fiber surfaces, there are only three methods available: plasma polymer deposition [12][13][14][15][16][17], electropolymerization or -deposition [8][9][10][11]18], and in situ chemical grafting reactions [19][20][21][22][23][24]. In earlier studies, we showed that it is possible to tune the carbon fiber chemistry and functionality and thereby their surface properties, i.e., hydrophilic/ hydrophobic character, by grafting suited monomers such as methacrylic acid (MAA) [25], 2-(N,N-dimethylamino) ethyl methacrylate (DMAEMA) [26] and various liquid crystalline monomers [27,28] onto carbon fibers via simple free radical bulk polymerization in the presence of the carbon fibers. The degree of grafting onto the surfaces can be adjusted by the amount of initiator used [29].…”
Section: Introductionmentioning
confidence: 99%